2021
DOI: 10.1186/s12955-021-01676-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and quality of life among adolescents in residential youth care: a cross-sectional study

Abstract: Background Residential youth care (RYC) institutions aim to provide care and stability for vulnerable adolescents with several previous and present challenges, such as disrupted attachments, wide-ranging adverse childhood experiences, mental health problems, and poor quality of life (QoL). To the best of our knowledge, the present study is the first to provide knowledge of the associations between perceived social support and QoL and to explore the potential moderating effect of perceived socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
3
11
0
1
Order By: Relevance
“…Enquanto para meninos, muitas vezes, a interação com amigos é fundamental, para as meninas, eventualmente e considerando o contexto, o apoio de adultos é mais relevante que de seus pares, impactando, portanto, de forma diferente nos escores de QVRS (Singstad et al, 2021).…”
Section: Discussionunclassified
“…Enquanto para meninos, muitas vezes, a interação com amigos é fundamental, para as meninas, eventualmente e considerando o contexto, o apoio de adultos é mais relevante que de seus pares, impactando, portanto, de forma diferente nos escores de QVRS (Singstad et al, 2021).…”
Section: Discussionunclassified
“…In addition, youth with a higher number of earlier experienced adversities and with the experience of maltreatment reported a lower QoL (Greger et al, 2016). Finally, Singstad et al (2021) showed that youth QoL is positively associated with perceived social support from TRC staff.…”
Section: The Present Studymentioning
confidence: 96%
“…The primary goal is to provide care and parenting substitution to young people to catch up with typical adolescent development regarding education and social life, reducing social and psychological problems of the residents and improving their QoL, through relationships with staff members and the resident group. TRCs in Norway are not considered to be treatment facilities, so direct services (e.g., mental health treatments) are provided by other agencies (Singstad et al, 2021).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This will provide more insight into the roles of different social support providers in improving the quality of life of adolescents. This study is important because adolescents who are in residential institutions need the importance of a lot of social support in their lives to improve their quality of life (Singstad et al, 2021 The use of information technology in implementing peer support needs to be developed. This study aims to create a peer group support-based platform for someone who experiences disorders due to drug use.…”
Section: "Examining the Effect Of Peer-support On Self-stigma Among Persons Living With Hiv / Aids"mentioning
confidence: 99%